Attuning and Queering SAMHSA's Strategic Prevention Framework. (18th August 2021) - Mendoza, Natasha S; Mackey, Cynthia; Harner, Vern; Jackson, Kelly
Abstract: To prevent substance use disorder (SUD) and its consequences, the Substance Abuse and Mental Health Services Administration developed the Strategic Prevention Framework (SPF). The SPF is a structured planning model that evaluates community behavioral health needs and facilitates prevention planning to address substance use concerns. Despite the SPF's stated foundation in cultural competency, the framework lacks appropriate guidelines to address systemic oppression of historically marginalized communities. Thus, the authors propose that an SPF based on a cultural attunement framework can enhance prevention-based social workers' ability to dismantle systemic barriers that create and perpetuate health disparities surrounding substance use and treatment for SUD. Using an example scenario, authors offer recommendations for social workers seeking to expand the SPF and fully actualize its application.